Non-Genetic Factors Affecting The Mortality Of Cage-Reared Broiler Rabbits (Oryctologus Cuniculus) Maintained Under Tropical Climatic Conditions Of Tamil Nadu - Kumar, V.Ramesh Saravana; Iniyah, K.; Sivakumar, K.; Thiruvenkadan, A.K.; Singh, D. Anandha Prakash; Ramesh, V.; Muralidharan, J.; Kannan , D. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The influence of non-genetic factors namely breed, sex, age, season and cause of death on the mortality of rabbits were studied utilizing a total of 835 mortality records over a period of 20 years. The study revealed that there is a significant difference (P
Keywords: Non-genetic Factors; Mortality; Broiler Rabbits (Oryctologus Cuniculus)